(untitled) (Kairaranga, 2018)
The role of teacher-aides (TAs) has increased in complexity and includes working to support students with challenging behaviour. This review examines the professional learning and development (PLD) needs of TAs who work with students with challenging behaviour and the types of PLD which are effective. TAs feel underprepared for behaviour work and want PLD which teaches specific behaviour strategies, is practical, hands-on and which can be translated into real-world contexts. Effective PLD focuses on specific interventions, is taught using modelling demonstrations, and gives TAs opportunities to practise skills and to receive feedback. In combination with practical demonstrations and performance feedback, follow-up training and coaching increases the fidelity with which behaviour interventions are implemented. PLD which aligns with the real needs of TAs, is delivered using accepted learning designs and which is sufficiently resourced is more likely to be effective. This paper examines some models of PLD which are effective.